Does co-teaching improve academic achievement for students with disabilities? A meta-analysis. (November 2021) - King-Sears, Margaret E.; Stefanidis, Abraham; Berkeley, Sheri; Strogilos, Vasilis
Abstract: Co-teaching consists of general and special education teachers who team to instruct students with and without disabilities in the same classroom. Additionally, some students with disabilities (SWD) receive instruction in special education settings. The purpose of this meta-analysis was to compare academic achievement of SWD in co-taught classes to achievement of SWD in special education settings. A comprehensive search of published and gray literature yielded 26 eligible studies with a total of 3, 714 SWD. Results indicate a moderate effect size ( g = 0.47) for students in co-taught settings compared to students in special education settings. Although the findings support SWD's academic achievement in co-taught classes, more information is needed to identify what distinguishes characteristics of the SWD in co-taught versus special education settings, as well as instruction in each setting. Factors related to results are described, including the lack of information about instructional practices and equivalency of students assigned to co-taught or special education settings. Implications for future researchers are provided, along with cautions about widespread placement of SWD in either setting without monitoring that effective instructional practices are in place, and that students receive specially designed instruction as stipulated on their Individualized Education Programs. Highlights: We conducted a meta-analysis about achievement of students with disabilities in two settings. We assessed factors that differentiate achievement between special and co-taught classes. Co-taught students benefitted more than their special education classroom peers. Co-teaching was more beneficial for secondary rather than for elementary students. Several studies omitted important descriptors thus more rigorous future studies are needed.